PENGARUH ANGKA MELEK HURUF DAN PENGANGGURAN TERHADAP KEMISKINAN DI PROVINSI SUMATERA BARAT - Putri, Lara Aziza (AL-ITTIFAQ Jurnal Ekonomi Syariah, 2025)
This study aims to examine the partial and simultaneous effects of literacy rates and unemployment levels on poverty across districts in West Sumatra Province during the period 2018–2022. Using a panel data regression approach, this research employs secondary data obtained from official statistical sources. The dependent variable is the poverty rate, while the independent variables consist of literacy rate and unemployment rate. The analysis reveals that the literacy rate has a negative and statistically significant influence on poverty, indicating that higher literacy levels contribute to reducing poverty in the region. Conversely, the unemployment rate exerts a positive and significant effect on poverty, suggesting that increased unemployment exacerbates the incidence of poverty. The F-test results further confirm that, collectively, literacy and unemployment significantly affect poverty levels. These findings underscore the importance of integrated policy measures aimed at improving educational outcomes while simultaneously addressing labor market inefficiencies to alleviate poverty. The study provides empirical support for regional development strategies that prioritize human capital investment and employment generation as key instruments in poverty reduction efforts. Furthermore, the research contributes to the literature on socioeconomic determinants of poverty by offering district-level insights within a specific provincial context in Indonesia.